Crystallization and preliminary X-ray analysis of mouse RANK and its complex with RANKL. - Walter, T; Liu, C; Huang, P; Zhang, S; Wedderburn, L; Gao, B; Owens, R; Stuart, D; Tang, P; Ren, J (2009)
The interaction between the TNF-family molecule receptor activator of NF-kappaB ligand (RANKL) and its receptor RANK induces osteoclast formation, activation and survival in the process of bone remodelling. RANKL-RANK also plays critical roles in T-cell/dendritic cell communication and lymph-node formation and in a variety of pathologic conditions such as tumour-cell migration and bone metastasis. Both the ectodomain of mouse RANKL and the extracellular domain of mouse RANK have been cloned, expressed and purified. Crystals of RANK alone and of RANK in complex with RANKL have been obtained that are suitable for structure determination.